Antibacterial and antiproliferative activities of the fresh leaf essential oil of Psidium guajava L. (Myrtaceae) - Silva, E. A. J.; Estevam, E. B. B.; Silva, T. S.; Nicolella, H. D.; Furtado, R. A.; Alves, C. C. F.; Souchie, E. L.; Martins, C. H. G.; Tavares, D. C.; Barbosa, L. C. A.; Miranda, M. L. D. (Brazilian Journal of Biology, 2018)
This study evaluated the antibacterial and antiproliferative activities of the essential oil of Psidium guajava leaves (PG-EO), traditionally used in folk medicine. The essential oil was obtained from fresh leaves by hydrodistillation, using a modified Clevenger apparatus. The major PG-EO chemical constituents were identified by GC-MS and GC-FID as being β-caryophyllene (16.1%), α-humulene (11.9%), aromadendrene oxide (14.7%), δ-selinene (13.6%), and selin-11-en-4α-ol (12.5%). The antibacterial activity of the essential oil of P. guajava leaves was determined in terms of its minimum inhibitory concentrations (MIC) using the broth microdilution method in 96-well microplates. PG-EO had moderate activity against Streptococcus mutans (MIC = 200 µg/mL), S. mitis (MIC = 200 µg/mL), S. sanguinis (MIC = 400 µg/mL), S. sobrinus (MIC = 100 µg/mL), and S. salivarius (MIC = 200 µg/mL). The antiproliferative activity was evaluated against different tumor cell lines: breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), and human gliobastoma (M059J). A normal human cell line (GM07492A, lung fibroblasts) was included. The antiproliferative activity was evaluated using the XTT assay and the results were expressed as IC50. The essential oil showed significantly lower IC50 values against MCF-7 and M059J lines than that obtained for the normal line, showing selectivity. Our results suggest that the essential oil of Psidium guajava L. has promising biological activities and can be considered a new source of bioactive compounds.

Este estudo avaliou as atividades antibacteriana e antiproliferativa do óleo essencial das folhas frescas de Psidium guajava (PG-OE), tradicionalmente utilizadas na medicina popular. O óleo essencial foi obtido por hidrodestilação das folhas frescas, utilizando aparelho do tipo Clevenger. Os principais constituintes químicos de PG-OE identificados por CG-EM e CG-DIC foram: β-cariofileno (16,1%), α-humuleno (11,9%), óxido de aromadendreno (14,7%), δ-selineno (13,6%) e selin-11-en-4α-ol (12,5%). A atividade antibacteriana do óleo essencial das folhas de P. guajava foi determinada em termo de sua concentração inibitória mínima (CIM) utilizando o método de microdiluição de caldo em microplacas de 96 poços. PG-OE apresentou moderada atividade contra Streptococcus mutans (CIM = 200 μg/mL), S. mitis (CIM = 200 μg/mL), S. sanguinis (CIM = 400 μg/mL), S. sobrinus (CIM = 100 μg/mL) e S. salivarius (CIM = 200 μg/mL). A atividade antiproliferativa foi avaliada frente a diferentes linhagens de células tumorais como: adenocarcinoma de mama (MCF-7), adenocarcinoma cervical humano (HeLa) e gliobastoma humano (M059J). Foi incluída uma linhagem celular humana normal (GM07492A, fibroblastos pulmonares). A atividade antiproliferativa foi avaliada utilizando o ensaio XTT e os resultados foram expressos como CI50. As linhagens MCF-7 e M059J mostraram valores significativamente mais baixos de CI50 do que os obtidos para a linhagem normal, mostrando seletividade. Nossos resultados sugerem que o óleo essencial das folhas frescas de Psidium guajava L. possui atividades biológicas promissoras e pode ser considerado como uma nova fonte de compostos bioativos.
Keywords: P. guajava; Essential oil; Oral pathogens; Antiproliferative activity; Óleo essencial; Patógenos orais; Atividade antiproliferativa